Arabis kaynakiae (Brassicaceae), a new species from South Anatolia, Turkey - Daşkin, Ruzi̇ye (Phytotaxa, 2013)
A new species, Arabis kaynakiae Daşkın (Brassicaceae), is described and illustrated from Turkey. The species grows on calcareous rocks in the Gülnar district (C4 Mersin province) in south Anatolia. It is allied to Arabis carduchorum, A. androsacea and A. alanyensis. The description, diagnostic characters and identification key are provided and its relationship with closely related taxa is discussed. The ecology and conservation status of the new species, in addition to the geographical distribution of the species and other related species are also presented.